2008
DOI: 10.1007/s12033-008-9038-7
|View full text |Cite
|
Sign up to set email alerts
|

An Epidermal Growth Factor-like Repeat of Del1 Protein Increases the Efficiency of Gene Transfer In Vitro

Abstract: In this paper, we found that Del1, an extracellular matrix protein secreted by embryonic endothelial cells, increases the efficiency of transfection in vitro. Conditioned medium containing Del1 increased transfection by the LacZ gene using several non-viral gene transfer systems, including lipoplex and polyplex methods. Experiments using deletion mutants and fragments of Del1 revealed that the third epidermal growth factor-like repeat (E3) of Del1 mediates the enhancement of gene transfer and, furthermore, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Proteins fused to the E3 and C1 domains are deposited in the ECM, where they accumulate. The E3 domain can also increase the endocytosis of transfected genes, and at high concentrations, E3 induces apoptosis (Kitano et al, 2008(Kitano et al, , 2010. We therefore examined the possible application of Del1 in cancer gene therapy by transfecting a squamous cell carcinoma line with cDNA encoding a FasL-E3C1 fusion protein.…”
Section: Del1 and Its Application In Cancer Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins fused to the E3 and C1 domains are deposited in the ECM, where they accumulate. The E3 domain can also increase the endocytosis of transfected genes, and at high concentrations, E3 induces apoptosis (Kitano et al, 2008(Kitano et al, , 2010. We therefore examined the possible application of Del1 in cancer gene therapy by transfecting a squamous cell carcinoma line with cDNA encoding a FasL-E3C1 fusion protein.…”
Section: Del1 and Its Application In Cancer Gene Therapymentioning
confidence: 99%
“…Molecules that initiate and enhance endocytosis are needed to improve endocytosis as a method for delivering exogenous molecules. Del1 protein is one such a factor that increases the efficiency of transfection in vitro and in vivo (Kitano et al, 2008). We have found that conditioned medium containing Del1 increases LacZ gene transfection using several non-viral gene transfer systems, including lipoplex and polyplex systems.…”
Section: E3 Enhances the Efficiency Of Gene Transfectionmentioning
confidence: 99%
“…Cell culture and reagents A431 cells (derived from human oral squamous cell carcinoma) were grown in serum-free 64 medium (60% Opti-MEM, 40% LCH-8 medium [Invitrogen, Carlsbad, CA]). Cells were cultured in an atmosphere of 5% CO 2 at 37 C. Recombinant fusion proteins with alkaline phosphatase (AP) were prepared as previously described (Kitano et al, 2008). Briefly, we generated several FIX deletion mutants by RT-PCR, which were cloned into the AP-tag4 vector (GenHunter, Nashville, TN) for production of APtagged FIX as a selected protein in CHO cells cultured in 64 media.…”
Section: Methodsmentioning
confidence: 99%
“…The CXDXXXXYXCXC sequence is present at the EGF1 domain in the light chain of FIX, referred to as EGF-F9 in this study. We previously reported that endocytosis is accelerated by EGF-F9 (Kitano et al, 2008). Presently, clathrin-dependent endocytosis is most commonly studied in endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“… 12 E3 has the ability to induce apoptosis and to increase gene transfer efficiency via induction of endocytosis. 13 , 14 C1 is essential for the deposition of Del1 in the extracellular matrix and could be used as a tool to deposit proteins into the extracellular matrix. 15 Therefore, it was expected that the E3C1 sequence of Del1 could deposit in the extracellular matrix in high concentration, induce apoptosis, and enhance the efficiency of subsequent transfections.…”
Section: Introductionmentioning
confidence: 99%